Perspectives on Prevention and Handling of Internal Bullying Al-Qur’an - Jelita, Pretty Jelita Oktovielda (EPIK: Edukasi Penerapan Ilmu Konseling, 2025)
Abstract Cases of bullying are commonplace in Indonesia. Bullying behavior itself will have an impact that can be detrimental to the victim physically, emotionally and psychologically. This research is aimed at producing individuals who have religious observance, have good morals, and have a positive impact on society through the perspective of the Al-Qur’an. This study uses a descriptive method using a literature study approach. The results of this study show that from an Islamic perspective, bullying is considered an unjust act in which the perpetrator will suffer a major sin. As explained in the word of Allah SWT. to overcome Bullying is Qs. Al Hujurat verse 11. The conclusion of this research is that bullying often occurs against individuals who have lower skills than others. Through Qs. Al Hujurat verse 11, Allah SWT forbids every individual to make fun of other individuals (Suhriyah). Keywords: Bullying, Al-Qur’an, and Prejudiced